The Probe Team [episode no. 282] - Lazaro, Cheche (Probe Productions, 1994)
The first part is about the one-peso levy on oil and gasoline in 1994. The Elsa Castillo film show is a controversial issue in the second part. The third part is an exclusive interview with a rock singer and musician during his concert in Manila.